Significance of Homocysteine in Glaucoma - Juenemann, Anselm; Rejdak, Robert; Hohberger, Bettina (Klinische Monatsblätter für Augenheilkunde, 2018)
Endothelial dysfunction and vascular dysregulation play a role in the multifactorial pathogenesis of glaucomatous optic nerve atrophy. Hyperhomocysteinemia is a risk factor for endothelial dysfunction and is associated with primary open-angle glaucoma as well as secondary open-angle glaucoma in the pseudoexfoliation syndrome. This paper reviews the literature on the association between homocysteine metabolism and glaucomatous disease and explains the possible role of hyperhomocysteinemia in the pathogenesis and progression of glaucoma. We discuss the role of exogenous modifiable risk factors for the prevention and therapy of glaucoma, as well as modification of these factors by changes in life style, such as weight reduction, changes in nutrition and physical activity. The roles of homocysteine in regulating the extracellular matrix, vasotoxicity, neurodegeneration, and epigenetics are explained. Prevention and therapy of glaucoma by regulation of homocysteine levels are discussed.
EVALuna2:34848